Faktor Pendorong dan Implikasi Perkembangan Pariwisata Spiritual di Kawasan Pariwisata Ubud - Putra Aditya, I Wayan; Ardika, I Wayan; Pujaastawa, Ida Bagus Gde (Jurnal Master Pariwisata (JUMPA); Volume 06, Nomor 01, Juli 2019DO - 10.24843/JUMPA.2019.v06.i01.p06, 2019)
The development of spiritual tourism activities in the Ubud Tourism Area based on the Tourism Area Life-Cycle Theory is at consolidation stage, which is seen from the many places that offer spiritual tourism activities both owned by local people and foreigners, resulting in price competition between these businesses.. The purpose of this research are to identify driving factors and implications of spiritual tourism development in the Ubud Tourism Area. This research is a qualitative descriptive study using observation and interviews for data collection methods. The theory used in this research are Contemporary Spiritual and Alternative Tourism Theory to explain the driving factors and implications sustainability resulting from spiritual tourism activities development related to. The driving factors include internal factors such as history and education as popular goals, external factors such as capitalism, world travel trends, and demand. Implications of this are implications for environmental, such as the conversion of residents' settlements and land conversion, for socio-cultural, such as changes in the consumption patterns of local people and revitalization of local spiritual activities, and for the economic, such as increased employment, increased income for spiritual service businesses, and increased ownership of local tourism businesses, where these implications require supervision by stakeholders so that they remain sustainable and provide optimal local communities benefits. Keywords: Implications, Spiritual Tourism, Ubud Tourism Area.